Implementasi Masalah Matematika melalui SPSS - Lukman Wildani; Pebri Yolanda; Satria Agung Laksana; edi supriyadi (Papanda Publisher, 2022)
This research is intended to be implemented primarily for final-year students. However, students interested in qualitative research can use this software. This research is qualitative. The data sources come from several articles, the internet, or their own data. Data we have obtained. From the research, quantitative data processing using SPSS software provides fast and accurate results in processing data using relatively simple software. The process of processing data is done manually